Radiation therapy after radical prostatectomy: A single-centre radiation oncology experience in trends of referral and treatment practices - Zimmermann, Michel; Taussky, Daniel; Delouya, Guila; Alenizi, Abdullah M.; Zorn, Kevin C. (Canadian Urological Association Journal, 2015)
Introduction: Our objective was to assess whether referral and treatment practices have changed since publication of the Southwest Oncology Group (SWOG) 8794 Trial in 2009, the first randomized study to demonstrate an overall survival advantage of adjuvant radiation therapy (RT) after radical prostatectomy (RP). Methods: We retrospectively reviewed all medical charts of men who received RT at our institution between 2004 and 2014 following RP. All RT was conducted by a single radiation oncologist (DT). We divided the cohort into 2 groups according to first referral date before or after the SWOG 8794 trial publication (i.e., before 2010 and after 2010). Results: Medical charts were available for 161/165 patients (97.6%). RP was performed at the same institution in 58% of cases. The median time between surgery and first referral for RT decreased significantly from 672 days (interquartile range [IQR] 295–1449) before 2010 to 300 days (IQR 225–1023) after 2010 (p = 0.04). This trend was associated with lower median prostate-specific antigen (PSA) at RT referral (0.26 μg/L [IQR 0.17–0.48] vs. 0.46 μg/L [IQR 0.25–0.90], respectively; p = 0.001). Androgen-deprivation therapy with RT nearly tripled over time from 13% before 2010 to 37% after 2010 (p = 0.003). Throughout the study period, the time interval between surgery and RT initiation was positively correlated with pT-stage (p = 0.001), Gleason score (p = 0.005) and PSA doubling time (p < 0.001). Conclusions: At our tertiary-referral academic institution, post-RP patients are notably referred earlier for RT and at lower PSA values compared to men treated prior to 2010. Further study is necessary to evaluate this impact on biochemical recurrence-free survival.